FACTORS ASSOCIATED WITH THE UTILIZATION OF TOOTH EXTRACTION AT THE RENGAS PULAU COMMUNITY HEALTH CENTER - T. Nurul Rian Ananda; Ermi Girsang; Thomson Parluhutan Nadapdap (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
Oral health remains a significant global challenge, with tooth extraction being a primary curative solution in primary care. Despite its availability, the utilisation of these services at Community Health Centres (Puskesmas) is influenced by various multifaceted factors. This study aims to analyse factors associated with the utilisation of tooth extraction services at the Rengas Pulau Community Health Centre, Medan. An explanatory sequential mixed-methods design was employed. The quantitative phase involved 110 adult patients selected via purposive random sampling, while the qualitative phase included 5 key informants for in-depth interviews. Data were analysed using Chi-Square tests, Multiple Logistic Regression, and thematic analysis.  Quantitative findings revealed that income (p=0.000; r=0.464), facilities and infrastructure (p=0.000; r=0.625), accessibility (p=0.000; r=0.648), and service quality (p=0.000; r=0.643) were significantly associated with service utilisation. Conversely, gender (p=0.115) and occupation (p=0.023) showed no significant relationship. Qualitative data reinforced these findings, highlighting that low-income patients utilised services more due to the National Health Insurance (BPJS), and perceived facility modernity significantly reduced dental anxiety.  Socio-structural factors (enabling and need factors) are more predictive of tooth extraction utilisation than predisposing demographic characteristics. Strengthening infrastructure and maintaining service excellence are critical to optimising primary oral healthcare.